A Stylistic Analysis of Online Political Commentaries of Edo 2020 Gubernatorial Election - Johnson Ajayi Ajiwoju (SALEE: Study of Applied Linguistics and English Education, 2023)
Abstract This study examined a stylistic analysis of online political commentaries of Edo 2020 gubernatorial election held on 19th September, 2020. The researcher selected 6 political commentaries from two online newspapers (Independent and Daily Post). The aim of this study was to analyze the collected data based on the objectives of the study that covers syntactic, phonological and graphological features found in the selected political commentaries. The analysis was hinged on Halliday’s Systemic Functional Grammar as its theoretical framework while the method was qualitative research analysis. Descriptive survey method was however employed to analyze the collected data. Therefore, the findings showed that there were instances of simple and non-simple sentences as well as declarative and imperative sentences. Moreover, phonological devices such as repetition, alliteration, assonance, and consonance were found therein. Also, foregrounded elements such as abbreviations or shortened words; symbols; and the use of small letters instead of capital letters to start sentences are evidential in some of the comments. Also, the commentators dominantly deploy deviational and non-deviational foregrounding to captivate readers’ attentions. On this note, the researchers therefore concluded that all these stylistic features make this study a unique one and thereby differentiating it from other stylistic analyses.